2020
DOI: 10.17263/jlls.759264
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Turkish EFL teachers’ perceptions of the factors affecting technology integration: A case study

Abstract: When technology is integrated into instruction in conjunction with effective teaching practices, it can enrich and enhance teaching and learning processes. With the changes in the nature of education wrought by advances in technology, teachers' key role in the successful integration of technology into the classroom has gained further significance. Therefore, it has become critical to understand the factors affecting teachers' technology integration. The present case study conducted with 70 university-level Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Similarly, Kim (2020) stated that limited access to online learning tools such as computers is one of the limitations of online learning. Previous studies (Francom, 2020;Onalan, & Kurt, 2020;Vann, Sanchez, & Santiago, 2015;Williams, Warner, Flower, & Croom, 2014) indicate that the access to resources, when technology became outdated or was sometimes limited, was one of the notable barriers of online learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kim (2020) stated that limited access to online learning tools such as computers is one of the limitations of online learning. Previous studies (Francom, 2020;Onalan, & Kurt, 2020;Vann, Sanchez, & Santiago, 2015;Williams, Warner, Flower, & Croom, 2014) indicate that the access to resources, when technology became outdated or was sometimes limited, was one of the notable barriers of online learning.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the argumentation of Groff and Mouza (2008) and Kim (2020) stating that teachers' lack of computer knowledge and experience are the two most notable challenges for teachers applying instructional technology in education. In the study conducted by Onalan and Kurt (2020), it was found that teachers perceived themselves as proficient in commonly-used programs such as wordprocessing and presentation software. However, teachers' perceived knowledge about using specialized software or special applications was found to be quite low.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for a larger tasks such producing, designing, structuring tasks for infants, calculating a large data for learners' report in the end of the semester, producing letters and so on, surely, the smartphone would not support this as much as the computer, the smartphone could be used, but through computer will be much more efficient because it built for that tasks [33]. However, without disregarding the valuable value computer has, but, if the computer and the smartphone are applied simultaneously in ELT practices then the process of teaching and learning, communication between students and teachers will be more smoothly [34], [35]. With the score results obtained, it could be stated that the teachers' knowledge of the latest technology of the English language teacher in junior high school level in Bitung city is high.…”
Section: Discussionmentioning
confidence: 99%
“…When technology is implemented in the classroom in tandem with appropriate instructional methods, learning processes can be improved and increased 11 . Technology integration is more than just teaching students how to use the basics of technology.…”
Section: Improving Student Performance Through Technologymentioning
confidence: 99%